Assessment of the groutability using secondary permeability index in an arid zone:a case study in Shitab dam site, se Iran - Nikpeyman, Yaser; Kargaranbafgh, Fariba; Ghasem, Mahboobeh; Sedaghat, Morteza (Italian journal of engineering geology and environment, 2019)
<span data-sheets-value="{"1":2,"2":"The water seepage through dams’ basement and abutments may result in catastrophic events at down-streams. Therefore, it is critical to seal dam foundation via reasonable methods. To decide a ground treatment strategy, one may not elaborate all necessary data-set especially in areas with very simple geologic properties. This study aims to evaluate the groutability in a very simple geologic condition. For this, the studies conducted along the Shitab Dam basement and abutments axis. The study area is located SE Iran, with an arid climate, where the mechanical weathering is extremely high. The investigation conducted through using 5 boreholes in the study area. The rock quality designation (RQD) index and Lugeon in-situ test were done. Additionally, the secondary permeability index (SPI) calculated using the field observations. The results revealed a serious complexity in engineering properties of the rock mass. Accordingly, the grout curtain pattern designed."}" data-sheets-userformat="{"2":15297,"3":{"1":0},"9":0,"10":1,"11":3,"12":0,"14":{"1":2,"2":0},"15":"Arial","16":8}">The water seepage through dams’ basement and abutments may result in catastrophic events at down-streams. Therefore, it is critical to seal dam foundation via reasonable methods. To decide a ground treatment strategy, one may not elaborate all necessary data-set especially in areas with very simple geologic properties. This study aims to evaluate the groutability in a very simple geologic condition. For this, the studies conducted along the Shitab Dam basement and abutments axis. The study area is located SE Iran, with an arid climate, where the mechanical weathering is extremely high. The investigation conducted through using 5 boreholes in the study area. The rock quality designation (RQD) index and Lugeon in-situ test were done. Additionally, the secondary permeability index (SPI) calculated using the field observations. The results revealed a serious complexity in engineering properties of the rock mass. Accordingly, the grout curtain pattern designed.